Philippine cargo guide, 1997. - Belgosa Business Communications, Inc. (Makati City Belgosa Business Communications, 1997)
Contents: Overview of cargo industry. Industry analysis. Industry guidelines. Brief on the Philippines. Seaport maps/schedule, Airport map/schedule. Organizations in the Philippine cargo industry. Product index and directory.
Purpose: A guide on the Philippine cargo industry. It presents valuable information from major government and private entities in the cargo business it also has a comprehensive directory of the products and services offered by the shipping and cargo industries.
Cover title
Keywords: Freight and freightage -- Philippines; Freight and freightage -- Philippines -- Directories